Laser-based techniques: Novel tools for the identification and characterization of aged microplastics with developed biofilm. (February 2023) - Pořízka, Pavel; Brunnbauer, Lukas; Porkert, Michaela; Rozman, Ula; Marolt, Gregor; Holub, Daniel; Kizovský, Martin; Benešová, Markéta; Samek, Ota; Limbeck, Andreas; Kaiser, Jozef; Kalčíková, Gabriela
Abstract: Microplastics found in the environment are often covered with a biofilm, which makes their analysis difficult. Therefore, the biofilm is usually removed before analysis, which may affect the microplastic particles or lead to their loss during the procedure. In this work, we used laser-based analytical techniques and evaluated their performance in detecting, characterizing, and classifying pristine and aged microplastics with a developed biofilm. Five types of microplastics from different polymers were selected (polyamide, polyethylene, polyethylene terephthalate, polypropylene, and polyvinyl chloride) and aged under controlled conditions in freshwater and wastewater. The development of biofilm and the changes in the properties of the microplastic were evaluated. The pristine and aged microplastics were characterized by standard methods (e.g., optical and scanning electron microscopy, and Raman spectroscopy), and then laser-induced breakdown spectroscopy (LIBS) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) were used. The results show that LIBS could identify different types of plastics regardless of the ageing and major biotic elements of the biofilm layer. LA-ICP-MS showed a high sensitivity to metals, which can be used as markers for various plastics. In addition, LA-ICP-MS can be employed in studies to monitor the adsorption and desorption (leaching) of metals during the ageing of microplastics. The use of these laser-based analytical techniques was found to be beneficial in the study of environmentally relevant microplastics. Graphical abstract: Image 1 Highlights: Microplastics were aged in freshwater and wastewater. Advanced laser-based techniques were tested for the detection of aged microplastics. Raman spectroscopy detected and classified aged microplastics. LIBS detected microplastics and biotic elements in the developed biofilm. LA-ICP-MS detected metals in microplastics and in the developed biofilm.